Closure of Complex Posterior Midline Defects After Spinal Surgery With Sensate Midline-based Perforator Flaps and the Long-term Results. Issue 23 (December 2015) - de Weerd, Louis; Solberg, Tore K.; Weum, Sven
Abstract : Study Design: Prospective study. Objective: Evaluating the use of a midline-based perforator flap for closure of complex midline defects after spine surgery complicated with implant exposure and deep subfascial infection. Summary of Background Data: Traditionally, muscle flaps are used to close complex defects after spine surgery complicated by exposed spinal implants and deep subfascial infections. There are no reports on the long-term results on the use of perforator flaps to close these defects. Methods: Information was prospectively registered of all patients in whom a medial dorsal intercostal artery perforator (MDICAP) flap was used for closure of a complex midline defect with exposed spinal implant and deep subfascial infection after spine surgery. Results: In 9 patients, 10 MDICAP flaps were used. All flaps survived with only 1 flap experiencing marginal flap necrosis. The flaps provided stable coverage of all defects and spinal instrumentation could be retained in all patients. The perforator flaps provided in all patients, except in the patient with a meningomyelocele, protective sensibility in the reconstructed areas. The mean postoperative hospital stay after closure of the defects was 10 days (range 4–21). During follow-up (mean 65 mo, range 7–106) only 1 patient developed an infection in the operated area which occurred 81 months postoperatively. None of the patients had any functional loss at the donor site of the flap. Conclusion: The medial dorsal intercostal artery perforator flap seems to be a reliable alternative for treatment of complex midline defects with exposed spinal implants and deep subfascial surgical site infections. Protective sensibility may be obtained in the reconstructed area with this flap. Donor site morbidity is minimal. In case of recurrence, complex reconstructive procedures using muscle flaps are still possible. The use of this perforator flap may contribute to shorter hospital stays and reduction of costs. Level of Evidence: 4